Cardioprotective effect of eicosapentaenoic acid during ischemia and reperfusion - Santa-Helena, Eduarda; Wally, Camila; Ribeiro, Joaquim de Paula; Votto, Ana Paula de Souza; Neves Gonçalves, Carla Amorim (Journal of Health & Biological Sciences, 2021)
Objective: In this work, rats isolated hearts were infused EPA before the ischemia period and during reperfusion for available get well in parameter relatives to redox reactions. Methods: The effect of EPA was tested on isolated hearts induced to ischemia and reperfusion, treatment occurred at different times (ischemia or reperfusion). Antioxidant capacity against peroxyl radicals, glutathione cysteine ligase activity, glutathione concentration, lactate dehydrogenase, and creatine kinase concentration was analyzed. Results: Hearts treated with eicosapentaenoic acid had the minor generation of species reactive oxygen and lipid damage after reperfusion. The GSH concentration was higher when the hearts were treated with eicosapentaenoic acid in the period of reperfusion. Conclusion: In conclusion, this study demonstrates that the dose of EPA (20μM) used before ischemia can act as a cardioprotective antioxidant molecule, prevented damage heart from ischemic and reperfusion injury.